EFFECT OF ELIMINATION OF NATIONAL EXAMINATION ON STUDENT GRADUATION STANDARD ASSESSMENT - Rizki Akmalia (Universitas Islam Negeri Sumatera Utara Medan, 2021)
Abstract: This paper discussed about the effect of the elimination of the National Examination on the standard of student graduation assessment starting from the introduction, the terminology of the national exam, the objectives, the positive and negative impacts of the implementation and elimination of the National Examination, the history of the National Examination from time to time, the standard of competence of educational unit graduates. Elementary and Secondary, the criteria for passing students after the National Examination were abolished and analysis of the elimination of the National Examination. The removal of the National Examination in 2020 yesterday, Nadiem Makarim issued a statement in Circular Number 4 of 2020 concerning the Implementation of Education Policy in the Emergency of the Spread of Corona Virus Disease (COVID-19) that UN participation was not a requirement for graduation or selection for higher education. So that in Circular No. 1 in 2020 explained that the graduation of students was determined through school exams based on the assessment of learning outcomes conducted by the teacher. Based on this statement, it could be interpreted that the graduation of students was in the hands of the teacher concerned.Keywords: National Examination (UN), Standard Assessment, Student Graduation